Determining the Prostate Cancer Road Map Hypothesis in 49 Countries: From Iron-Deficiency Anemia (IDA) to Death - Cornelli Umberto; Belcaro Giovanni; Recchia Martino (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Background: During the follow up analysis of the San Valentino (Italy) screening of cardiovascular diseases of death due to prostate cancer (PCa) in 2016 had in common iron deficiency anemia (IDA) in 2000. Aims: The analysis was conducted on all available data within the WHO records concerning total mortality for PCa in term of ASDRs (Age-Standardized-Death Rate x 100000 population) compared to ASDRs of IDA and diseases possibly causing IDA considering the year 2000. Methods: An analysis was conducted in 49 countries to determine the relationship between PCa, IDA and other 16 variables possibly connected with IDA. Data were retrieved from the WHO records (2018) using the ASDRs (Age-Standardized Death Rate x 100000 population) in 49 countries limited to the years 2000, 2010 and 2016. The 49 selected countries (SC) were those considered by WHO “with high completeness and quality of cause-of-death assignment” and “may be used for priority setting and policy evaluation”. PCa, IDA, and 16 diseases: tuberculosis, gonorrhea, syphilis, chlamydia in females, other sexually transmitted diseases (STDs in both genders), diarrheal diseases, gastric ulcers, cirrhosis, IDA, HIV, digestive diseases, respiratory infections, alcohol, and drugs addictions. The correlations with PCa were calculated using the Cluster analysis followed by the Multivariate analysis and the Residual Normal Quantile Plot. Results: IDA, HIV, chlamydia in females, and digestive diseases were significantly correlated with PCa. All the other variables resulted not correlated. In terms of mean values, the total ASDRs were significantly improved (-25%). However, in most of the diseases, the variances were very high, indicating that the averages and % reductions have to be considered with prudence. Conclusions: The road map of PCa seems to be IDA, immune depression, followed by infections caused by chlamydia. Digestive diseases- other than gastric ulcers and cirrhosis- are only minimally predictive. Chlamydia vaccination is suggested as a possible solution to protect from PCa. Prospective, long-term studies should be considered